2019
DOI: 10.1016/j.childyouth.2018.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Parenting influences on adolescent sexual risk-taking: Differences by child welfare placement status

Abstract: Positive parenting behaviors and parent-child relationships reduce sexual risk-taking among youth, but these associations may differ for adolescents in the child welfare system. Using two cohorts of a national longitudinal dataset of youth, the authors employed linear probability modeling to investigate associations of caregiver-child closeness, monitoring, and dating communication with youth’s sexual initiation, sexual partners, and unprotected intercourse over the subsequent 12 months. Moderation by placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…(2015), which state that parents who raise children positively will reduce deviations in sexual orientation in children. Furthermore, the results of this study are also in line with the results of the research by Potter and Font (2019), which states that in the process of parenting, parents who have good, warm, and low relationships with children will reduce the risk of deviant behaviour, especially deviations in sexual orientation.…”
Section: Discussionsupporting
confidence: 88%
“…(2015), which state that parents who raise children positively will reduce deviations in sexual orientation in children. Furthermore, the results of this study are also in line with the results of the research by Potter and Font (2019), which states that in the process of parenting, parents who have good, warm, and low relationships with children will reduce the risk of deviant behaviour, especially deviations in sexual orientation.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, conversations and education, when they occurred, largely focused on warning signs of abuse, risks, and presumed negative outcomes which augmented already existing stigma and negative self-concept. Not only did the lack of open and non-judgmental conversations represent a missed opportunity for ongoing, informal education about healthy relationships, but the youth-caregiver disconnect itself contributed to vulnerability for IPV ( Katz et al, 2020 ; Potter & Font, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, placement stability ( Jonson-Reid et al, 2007 ), positive parenting practices and closeness to caregivers ( Garrido & Taussig, 2013 ) have been identified as protective factors against IPV. Potter and Font (2019) showed that caregiver closeness irrespective of placement type reduced the likelihood of youth engaging in sexual behaviors such as unprotected intercourse and sexual activity with new partners. Garrido and Taussig (2013) hypothesized that positive parenting practices may provide a template for healthy relationships and a safe space to share experiences and build skills, such as emotion regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Connectedness with caring adults is one of the most important protective factors in adolescents' lives and is associated with improved sexual health outcomes and decreased physical and sexual dating violence victimization (Steiner et al, 2019). Accordingly, connectedness with caregivers irrespective of placement type has the potential to reduce sexual risk behaviors such as unprotected intercourse among youth in care (Potter & Font, 2019). Unfortunately, many youth in foster care feel disconnected from family, friends, and community, and child welfare professionals and foster caregivers report discomfort talking with youth about sexuality and relationships (Harmon-Darrow et al, 2020;Serrano et al, 2018).…”
Section: Background: Defining the Challengementioning
confidence: 99%